Design of Waveform Set for Multiuser Ultra-Wideband Communications - Yusoff, Mohd Amaluddin Bin (Curtin University, 2016)
The thesis investigates the design of analogue waveform sets for multiuser and UWB communications using suitably chosen Hermite-Rodriguez basis functions. The non-linear non-convex optimization problem with time and frequency domains constraints has been transformed into suitable forms and then solved using a standard optimization package. The proposed approach is more flexible and efficient than existing approaches in the literature. Numerical results show that orthogonal waveform sets with high spectral efficiency can be produced.